GENERALISASI INVERS SUATU MATRIKS YANG MEMENUHI PERSAMAAN PENROSE - ImronArdi Gunawan; Solichin Zaki (Jurnal Matematika, 2012)
Generalized inverse is an extension of the concept of inverse matrix. One type of generalized inverse of a matrix of size (m × n) with elements of the complex number is the Moore Penrose inverse is denoted by A+ . Moore Penrose inverse is the inverse of the matrix which must satisfy the four equations called Penrose equations. Generalized Inverse whereas only satisfy some (not all) of the four Penrose equations are divided into classes based on the number of equations that can be met Penrose, {1}-inverse, {1,2}-inverse, {1,2.3}-inverse, dan {1,2,4}-inverse.